Rozważania wokół strategii w profilaktyce zaburzeń mowy = Considerations around strategy in the prevention of speech disorders - Gebreselassie, Jolanta (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Analysis of local and nationwide researches conducted over decades shows that number of children with speech disorders increases. According to some researches 76% Polish children have speech disorders of different types. It is believed that effective prevention, aimed especially at children, is an optimal way of limiting phenomena that are considered as unfavourable.
Keywords: profilaktyka zaburzeń mowy; profilaktyka uniwersalna; profilaktyka selektywna; profilaktyka wskazująca; strategie profilaktyczne; prevention of speech disorders; universal prevention; selective prevention; indicating prevention; preventing strategies